2018
DOI: 10.15232/pas.2018-01747
|View full text |Cite
|
Sign up to set email alerts
|

Blood serum mineral element concentrations of weaned Montana ram lambs and their relationship with water quality characteristics

Abstract: Clinical and subclinical trace mineral deficiencies can limit productivity in western sheep production systems. The objective of this research was to determine the proportion of ranches that supplemented with trace minerals and to quantify serum trace mineral concentrations in ram lambs after weaning across Montana with particular emphasis on Se and Zn. Serum samples (n = 214) were collected from ram lambs 8 to 10 mo of age (52.8 ± 16 kg) at 21 ranches throughout Montana and analyzed for Co, Cu, Fe, Mn, Mo, Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
9
1
Order By: Relevance
“…Sheep, as a grazing animal, are susceptible to nutritional deficiencies, because of local variation in the concentrations of these elements in pasture plants. The average Cu blood concentration of ewes in this study was in the adequate range which is 0.70-1.00 µg/dl according to Page et al (2018). According to the NRC (2007) recommendation for Zn, Fe, Cu, Se, Mo and Co in feeds for sheep the range is 20-33 mg/kg, 30-50 mg/ kg, 7-11 mg/kg, 0.1-0.2 mg/kg, 0.5 mg/kg and 0.10-0.20 mg/kg dry matter, respectively.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Sheep, as a grazing animal, are susceptible to nutritional deficiencies, because of local variation in the concentrations of these elements in pasture plants. The average Cu blood concentration of ewes in this study was in the adequate range which is 0.70-1.00 µg/dl according to Page et al (2018). According to the NRC (2007) recommendation for Zn, Fe, Cu, Se, Mo and Co in feeds for sheep the range is 20-33 mg/kg, 30-50 mg/ kg, 7-11 mg/kg, 0.1-0.2 mg/kg, 0.5 mg/kg and 0.10-0.20 mg/kg dry matter, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…The serum Co concentrations in adult cattle are typically between 0.3 and 1.1 ng/ml (Herdt and Hof 2011), which is more compared to the present research. However, Page et al (2018) reported adequate ranges of the blood serum concentration for Co > 0.10 ng/ml. In the present study low concentrations of Cd and As were determined.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Blood Cu, Zn and Se were well below reference values for whole sheep blood (7). Studies have indicated that deficiencies of Se and Zn in feed and sheep blood require supplementation (1,10).…”
Section: Resultsmentioning
confidence: 90%
“…Changes in external factors, including daily feed or environmental stressors, can be observed in the blood of the affected animals. A survey conducted to quantify serum mineral concentrations in Montana ram lamb populations indicated that approximately 9.5% of ranch flocks were deficient and 57.1% were marginally deficient in Zn [ 24 ]. This can apply to other mineral profiles as well.…”
Section: Discussionmentioning
confidence: 99%